Respostas
respondido por:
5
Vamos primeiramente determinar o 6° termo dessa PG.
a₁ = 7
a₂ = 14
n = 6
q = 14 / 7 = 2
a₆ = a₁ * q^n-1
a₆ = 7 * 2⁶⁻¹
a₆ = 7 * 2⁵
a₆ = 7 * 32
a₆ = 224
Soma dos termos da PG:
S₆ = a₁ * (q^n - 1) / q - 1
S₆ = 7 * (2⁶ - 1) / 2 - 1
S₆ = 7 * (64 - 1) / 1
S₆ = 7 * 63 / 1
S₆ = 441 / 1
S₆ = 441
Espero ter ajudado. Valeu!
a₁ = 7
a₂ = 14
n = 6
q = 14 / 7 = 2
a₆ = a₁ * q^n-1
a₆ = 7 * 2⁶⁻¹
a₆ = 7 * 2⁵
a₆ = 7 * 32
a₆ = 224
Soma dos termos da PG:
S₆ = a₁ * (q^n - 1) / q - 1
S₆ = 7 * (2⁶ - 1) / 2 - 1
S₆ = 7 * (64 - 1) / 1
S₆ = 7 * 63 / 1
S₆ = 441 / 1
S₆ = 441
Espero ter ajudado. Valeu!
respondido por:
0
Faça assim;
P.G.(7, 14,...)
q=14=2
7
ou P.G.(7, 14, 28, 56, 112, 224)= 441
+ + + + +
P.G.(7, 14,...)
q=14=2
7
ou P.G.(7, 14, 28, 56, 112, 224)= 441
+ + + + +
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás